1-(12-Azido-n-dodecyl)-4-[(1,5-dibenzyl-2,4-dioxo-2,3,4,5-tetrahydro-1 H-1,5-benzodiazepin-3-yl)methyl]-1H-1,2,3-triazole - Jabli, H.; Chahdi, F.O.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The reaction of 1,5-dibenzyl-3-propargyl-1,5-benzodiazepine-2,4-dione with 1,12-diazido-n-dodecane in the presence of catalysts leads to the formation of the title compound, C(38)H(46)N(8)O(2). The seven-membered diazepinyl ring adopts a boat conformation with the azidododecyltriazolylmethyl-bearing C atom as the prow and the fused-ring C atoms as the stern. The octyltriazolylmethyl substituent occupies an axial position.